ASSOCIATION OF BONE MINERAL PROFILE WITH RESTLESS LEG SYNDROME IN PATIENTS WITH END STAGE RENAL DISEASE. - Sultan, Sajid; Nasir, Kiran; Qureshi, Ruqaya; Dhrolia, Murtaza; Ahmad, Aasim (Journal of Ayub Medical College Abbottabad, 2022)
Background: Restless leg syndrome (RLS) is one of the problem hemodialysis patients may encounter. This study was done to find out the association of restless legs syndrome (RLS) in end stage renal disease patients with serum calcium, phosphorus and parathyroid hormone levels. Methods: This cross-sectional observational study was done at The Kidney Centre, postgraduate Training Institute Karachi, Pakistan from Jan to June 2020. One hundred and twelve patients on three per week hemodialysis for more than three months at our hemodialysis centre were face to face interviewed as per International Restless Legs Syndrome Study Group criteria (IRLSSG) for the presence of RLS symptoms. Their demographic data and laboratory values were recorded from history chart and computer records. The bone mineral profile in this study includes serum calcium (corrected for albumin), serum phosphate levels and serum intact Parathyroid hormone (iPTH) levels. Statistical analyses were done by using SPSS-21. Results: In our study, 38.4% patients had RLS. Serum phosphorus levels were significantly higher in patients with RLS as compared to those who didn’t have RLS. No significant association of serum calcium and Parathyroid hormone (PTH) levels with RLS was found. Conclusion: There is a high prevalence of RLS in ESRD patients as compared to general population. Serum phosphorus levels need to be observed and corrected along with maintenance of calcium and PTH levels to improve symptoms of RLS in these patients.